Importance of the product country-of-origin factor on purchasing process in the context of globalisation - Urbonavičius, Sigitas; Gineikienė, Justina (Ekonomika, 2009)
Globalization is raising the country-if-origin importance question in the new light. It seems that the importance of country-of-origin (COO) factor has to go down, since both manufacturing and purchasing processes are under influence of overall globalization. In addition to this, many globally offered brands may be no longer associated with a specific country of their origin. From the other side, there are still strong attitudes of buyers observed about ‘domestic’ versus ‘foreign’ products, as well as about attitudes towards various countries. If these attitudes work as strong element within the COO factor, the importance of COO in the context of globalization would remain rather big. The objective of the paper is to explore the COO effect on the purchasing process in the context of globalization. The specific of Eastern European context is reflected through empirical exploratory research that was performed in Lithuania. The analysis suggests that perhaps some other elements have to be also included into studies of COO importance on purchasing behaviour. The authors propose that a less yet studied trait within consumers – country animosity – should receive more attention. It seems that in certain situations a product’s origin can affect consumer buying decisions rather independently from judgments’ of other characteristics of a product. The article formulates a model that incorporates country-of-origin animosity and purchasing moderators for further studies of the issue.